A FINGERPRINT BASED STUDENTS ATTENDANCE MANAGEMENT SYSTEM FOR OLABISI ONABANJO UNIVERSITY - Olasupo, A. O.; Ademiluyi, O. S.; Usman, M. A.; Abdullah, K.-K. A.; Olubanwo, O. O.; Ayo, F. E.; Ojumadu, U. H.; Salami, E. O.; Ibironke, T. E. (FUDMA JOURNAL OF SCIENCES, 2022)
The development of attendance was motivated by the necessity to keep track of who was there in a certain location at any given moment for future reference. Attendance is defined as the awareness of persons present at a specific location at a specific time for a previously scheduled event. Keeping and managing attendance records efficiently is critical for student evaluation. All formal institutions of learning place a high value on class attendance, which is so important that students who do not reach the class attendance threshold are not allowed to appear for exams. Traditional attendance marking techniques are prone to human error and time demanding for both students and lecturers during class. The old attendance system has various drawbacks, including lost attendance sheets, impersonation, time waste, insecurity, and lack of precision. As a result, by utilizing the unique qualities of fingerprint technology, a smart solution to the challenges connected with the traditional attendance system is required. As a result, the article devised, designed, and deployed a fingerprint-based attendance management system for students. The system’s development model was the Software Development Life Cycle (SDLC). To record and verify students’ fingerprints, a digital persona fingerprint scanner was utilized, and the Graphical User Interface (GUI) was created using the window forms application of the Visual Studio Integrated Development Environment (IDE). The back-end design was created using the C# programming language and the Structure Query Language (SQL) server. The system’s logic was implemented in C#, and the SQL server was utilized as the